Using Educational Escape Room to Increase Students’ Engagement in Learning Computer Science - Georgina Dimova; Maja Videnovik; Vladimir Trajkovik (Ss. Cyril and Methodius University in Skopje, Faculty of Computer Science and Engineering, Republic of North Macedonia, 2020)
This paper presents the process of creating and implementing a large-scale experiment that involves students from more than 10 primary schools using the escape room style educational game in the classroom. The potential benefits and issues related to using technology in integrating this kind of games in education are explored and elaborated in the paper. An escape room is a game played by a team of people. They have to 'escape' from a room filled with challenges within a given time limit. In order to succeed, the players must solve the challenges using different hints and strategies. If these challenges incorporate education materials, students will have to master these materials, which will enhance their learning and increase their engagement.